Disposable Component Selection in Extracorporeal Life Support: A Cost Analysis. Issue 9 (11th December 2020) - Stokes, John W.; Gannon, Whitney D.; Tipograf, Yuliya; Ukita, Rei; Warhoover, Matthew; Rice, Todd W.; Shah, Ashish S.; Bacchetta, Matthew
Abstract : Supplemental Digital Content is available in the text. Abstract : Extracorporeal life support (ECLS) is a resource-intensive technology. Disposable components are modifiable through device selection. Cost analysis tools are needed to inform cost-conscious device selection. We generated a disposable cost analysis to forecast estimated costs of device disposables that included an assumption table, net present value (NPV) analysis, and sensitivity analysis to examine device disposable costs over 5 years with different case volumes and device mixes. To demonstrate the function of the analysis, we included four device options using the following assumptions: 100 cases in year 1, 2.5% case growth rate, 10% discount rate, and 5, 000 incremental cost (Device 4 only). Using estimated device costs of 3, 000, 12, 000, 13, 000, and 20, 000 and device mix percentages of 65%, 8%, 25%, and 2% for Device 1, 2, 3, and 4, respectively, the 5 year unadjusted and NPV of disposable device costs were 3, 691, 000 and 2, 765, 000, respectively. The sensitivity analysis incorporated six separate models with different device mix percentages. The highest and lowest estimated costs were found in Model F (75% Device 3 and 25% Device 4; NPV = 6, 64, 400) and Model B (100% Device 1; NPV = 1, 246, 000) respectively. Extracorporeal life support programs may apply this disposable cost analysis tool to reduce programmatic costs.